Sexual dysfunction and depression in premenopausal women with mucocutaneous Behçet's disease. (19th October 2012) - Yetkin, D. O.; Celik, O.; Hatemi, G.; Kadioglu, P.
Abstract: Aim: The aim of this study was to investigate depression and sexual dysfunction in female patients with mucocutaneous Behçet's disease (BD). Methods: Twenty‐five consecutive, sexually active premenopausal female patients with mucocutaneous BD (mean age: 34.76 ± 4.61 SD years) followed at a rheumatology outpatient clinic were enrolled into the study. The control group consisted of 27 age‐matched (mean age: 37.0 ± 4.6 SD years), sexually active, healthy volunteers. The Female Sexual Function Index (FSFI) and Beck Depression Inventory (BDI) were used for sexual and psychiatric assessment. Results: Depression was found in four of 27 (14.8%) in the control group and eight of 25 (32%) in the BD group ( P  =   0.01). The median total FSFI score for patients with BD was 21.85 (interquartile range [IQR]: 18.25–27.9) and for healthy controls, 27 (IQR 21.5–29.3; P  =   0.03). Female sexual dysfunction was diagnosed in 14 of 25 (56%) in the BD group and in 11 of 27 (41%) in the control group ( P  =   0.27). The pain domain was significantly higher in the BD group at 5.6 (4.4–6.0) than in the control group at 4.4 (3.2–5.5; P  =   0.03). None of the other domains (desire, arousal, lubrication, orgasm and satisfaction) of the BD and control groups were different. There were no statistically significant differences between the FSFI, BDI scores and presence of genital ulceration in the BD patients. Conclusion: Depression and FSD were more common in the patients with BD than in the healthy subjects. This might have been a result of the depressive effect of chronic disease as well as BD and low androgen levels.